Shoot Heterogeneity Effects on Shiraz/Richter 99 Grapevines. I. Vegetative Growth - Cloete, H.; Archer, E.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2017)
In this study the vegetative growth parameters of normally developed and underdeveloped shoots were compared in an attempt to quantify shoot heterogeneity in a Shiraz/Richter 99 vineyard. A field trial was performed in the Stellenbosch area,Western Cape, South Africa. Comparisons based on certain vegetative growth parameters were made between normally developed and underdeveloped shoots from both shaded and well-exposed canopies. The longer primary shoots of the normally developed shoots matured earlier in the season, with less apparent competition between shoot lignification and grape ripening. Reserves were more evenly distributed in these shoots. Total starch content over the whole shoot was found to be higher in the normally developed shoots, particularly when well exposed. More and longer secondary shoots occurred on the normally developed shoots than on the underdeveloped shoots. No difference was found in the number of primary leaves (leaves on primary shoots) between normally developed and underdeveloped shoots, although the leaf area was much larger in the case of the former. Normally developed shoots had more and larger secondary leaves (leaves on secondary shoots), while all the leaves that developed in the shaded canopies were found to be larger than those in the well-exposed canopies with a higher leaf area:mass ratio. The normally developed shoots seemed to have a greater potential for producing a higher yield, with better quality, than the underdeveloped shoots, as they have a more desirable leaf area composition in addition to a larger total leaf area per shoot.